2017
DOI: 10.1016/j.celrep.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The HECT Family Ubiquitin Ligase EEL-1 Regulates Neuronal Function and Development

Abstract: Summary Genetic changes in the HECT ubiquitin ligase HUWE1 are associated with intellectual disability, but it remains unknown whether HUWE1 functions in post-mitotic neurons to affect circuit function. Using genetics, pharmacology and electrophysiology, we show that EEL-1, the HUWE1 ortholog in C. elegans, preferentially regulates GABAergic presynaptic transmission. Decreasing or increasing EEL-1 function alters GABAergic transmission and excitatory/inhibitory (E/I) balance in the worm motor circuit, which le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 57 publications
(90 reference statements)
5
50
0
Order By: Relevance
“…This includes sensory neurons, the nerve ring (a central bundle of hundreds of axons), and the motor neurons of the nerve cord ( Fig. 1c) [18]. The broad expression of Huwe1 in adult mammalian and C. elegans nervous systems is consistent with Huwe1 having widespread, important roles in the nervous system, which we discuss further.…”
Section: Huwe1 Protein Composition and Nervous System Expressionsupporting
confidence: 53%
See 1 more Smart Citation
“…This includes sensory neurons, the nerve ring (a central bundle of hundreds of axons), and the motor neurons of the nerve cord ( Fig. 1c) [18]. The broad expression of Huwe1 in adult mammalian and C. elegans nervous systems is consistent with Huwe1 having widespread, important roles in the nervous system, which we discuss further.…”
Section: Huwe1 Protein Composition and Nervous System Expressionsupporting
confidence: 53%
“…The RPM-1/FSN-1 ubiquitin ligase complex is an important regulator of axon termination in C. elegans [35,36], and functions as both a ubiquitin ligase and a signaling hub to affect numerous downstream signaling pathways [31,[37][38][39][40][41][42]. In two different eel-1 (lf) mutants, low levels of axon termination defects were observed in two types of neurons, the SAB motor neurons and the mechanosensory neurons that sense gentle touch [18]. Interestingly, eel-1; fsn-1 double mutants had strong enhancer effects indicating that EEL-1 and FSN-1 function in parallel pathways to regulate axon termination.…”
Section: Huwe1 Influences Axon Developmentmentioning
confidence: 99%
“…Our laboratory has used Retigabine with C. elegans in the past to show that human seizure therapeutics can successfully be used to alter recovery time in invertebrates; however, regarding N2, the drug must be used in conjunction with a chemical convulsant to induce an effect (Opperman et al 2017; Risley et al 2016). We hypothesize this is due to the increased seizure threshold for N2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals have shown that they play a key role in protein degradation and DNA damage related. In recent years, studies have found that human HECT E3s is also closely linked to the occurrence of various diseases such as cancer [8,36,37].…”
Section: Hect Ubiquitin Protein Ligasementioning
confidence: 99%